2013
DOI: 10.3168/jds.2012-5781
|View full text |Cite
|
Sign up to set email alerts
|

Timing of supplementation alters grazing behavior and milk production response in dairy cows

Abstract: Offering feed supplements to grazing dairy cows results in substitution of pasture; however, previous data indicate that the time at which concentrate supplements are offered might affect the level of substitution. These data indicated that cows grazed more intensely presunset, regardless of the amount of supplement offered. It was, therefore, hypothesized that substitution rate would be less, and response to supplement greater if cows received their supplement at the p.m. rather than the a.m. milking. Forty-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 21 publications
2
30
1
Order By: Relevance
“…Neuroendocrine factors are secreted from various tissues to inform the brain of the energy status of the cow . When cows consume a supplement, satiety signals cause the cows to graze for less time (12 min/kg of DM concentrate consumed; Bargo et al, 2003;Sheahan et al, 2011) and consume fewer bites/min (i.e., a lower bite rate; Sheahan et al, 2013). Nevertheless, the estimated substitution rate in the present study is high relative to that reported in the literature for well-managed grazing systems (Stockdale, 2000;Linnane et al, 2004;Sheahan et al, 2011).…”
Section: Feeding Intensity and Profitability Milk Production And Pacontrasting
confidence: 51%
“…Neuroendocrine factors are secreted from various tissues to inform the brain of the energy status of the cow . When cows consume a supplement, satiety signals cause the cows to graze for less time (12 min/kg of DM concentrate consumed; Bargo et al, 2003;Sheahan et al, 2011) and consume fewer bites/min (i.e., a lower bite rate; Sheahan et al, 2013). Nevertheless, the estimated substitution rate in the present study is high relative to that reported in the literature for well-managed grazing systems (Stockdale, 2000;Linnane et al, 2004;Sheahan et al, 2011).…”
Section: Feeding Intensity and Profitability Milk Production And Pacontrasting
confidence: 51%
“…Sheahan et al . () observed a tendency for an increased marginal milk production response (kg of milk/kg of supplement) in cows supplemented in the morning rather than the evening. This is contrary to Trevaskis et al .…”
Section: Discussionmentioning
confidence: 96%
“…As the silage mixture contained corn silage and grass silage which was made from more maturated grass than pasture grass, total contents of rumen digesta before evening grazing in our study could be greater compared to the cows studied by Sheahan et al . (). Physical rumen distention is another important factor constraining forage intake (Allen ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations